Identifikasi Potensi Bakteri Asam Laktat dari Dangke Susu Kuda Liar di Nusa Tenggara Barat Sebagai Kandidat Probiotik Lokal - Komalasari, Husnita; Anam Afgani, Chairul; Melandani, Astri (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2025)
Dangke is a traditional food from Enrekang, South Sulawesi, and in the West Nusa Tenggara (NTB) region, dangke is also produced from local food which is wild horse milk. This study aimed to identify and characterize the microbiological profile of dangke of NTB to assess its potential as an indigenous probiotic candidate. The research used an experimental method with a Completely Randomized Design (CRD), considering the area of sample origin as the factor with Tukey's post-hoc test was applied at a 5% significance level. Multivariate Principal Component Analysis (PCA) was conducted using XLSTAT to map the microbiological characteristics. The results showed that sampling areas significantly affected microbiological properties such as total lactic acid bacteria (LAB), growth tolerance to bile salt, NaCl, and pH 2.5, as well as antimicrobial activity against E. coli and S. aureus. PCA revealed that dangke from Bima and Sumbawa had similar characteristics, which differed from those of Lombok and Dompu. These findings indicated that LAB from wild horse milk dangke had potential as indigenous probiotic candidates. In conclusion, this study identified and mapped the regional differences in dangke characteristics and highlighted their probiotic potential.